On the Way to the Next Stage of Mechanics - Parfentyev Nikolay; Parfentyeva Natalia; Maignan Schubert (Budapest International Research in Exact Sciences (BirEx) Journal, 2023)
The results of real experiments according to the Wheeler scheme prove the influence of the future on the behavior of elementary particles in the present. Interpretation of the results of experiments on the basis of ideas about the interaction of bodies in time leads to the following conclusions: 1. The force of inertia corresponds to the general definition of force as a measure of interaction. 2. Newton's second law becomes a consequence of the third, 3. The problem of correspondence between gravitational and inertial mass has been solved, 4. General expressions for the force of inertia leading at low speeds to the classical formulas of accelerated motion and circumferential motion are given. Within the framework of the developed method, an expression is given for the force of interaction, which takes on a real value, at the moment when the body moves at a speed exceeding the speed of light. The expression for this force differs in sign from the force of inertia. A hypothesis is put forward that the nature of such forces is a temporary interaction of charge. The application of Einstein's formula for a moving mass in this case organically explains the existence of charges of different signs. Modulo, both forces are equalized in a range of speeds close to the speed of light. It is supposed to use the adopted approach to describe the nature of elementary particles.